Comorbid Sleep Disturbance in Adolescents with Functional Abdominal Pain. Issue 4 (4th July 2021) - Murphy, Lexa K.; Palermo, Tonya M.; Tham, See Wan; Stone, Amanda L.; Han, Gloria T.; Bruehl, Stephen; Garber, Judy; Walker, Lynn S.
ABSTRACT: Objective/Background: Sleep disturbances have been commonly reported as comorbid in youth with pain conditions, but prior research specific to functional abdominal pain (FAP) is limited. This study describes individual factors associated with increased risk for sleep disturbance and characterizes the relationship between sleep disturbance and pain-related variables. Participants: Participants included 278 adolescents (age 11 to 17 years, M age = 15 years; 89% Caucasian; 65% female) with FAP. Methods: Participants reported on sleep disturbances, abdominal pain severity, functional disability, somatic symptoms, and healthcare utilization. Results: Female adolescents reported greater sleep disturbance than male adolescents ( t (276) = 5.52, p < .001, Cohen's d = 0.70) and increased age was associated with greater sleep disturbance ( r =.20, p =.001). In hierarchical regressions controlling for age, sex, and abdominal pain, greater sleep disturbance was significantly associated with greater functional disability (β =.32), non-gastrointestinal somatic symptoms (β =.35), and emergency department visits (β =.29). Conclusions: Results suggest that sleep disturbance is common and should be assessed in youth presenting with FAP and may be a potential target for intervention.